Tighter Blood Pressure Control Is Associated with Lower Incidence of Erectile Dysfunction in Hypertensive Men. Issue 3 (1st March 2019) - Hsiao, Wayland; Bertsch, Ruth Ann; Hung, Yun-Yi; Aaronson, David S.
Abstract: Introduction: Tighter blood pressure control is widely thought to be associated with better erectile function, although the preponderance of data is limited to dichotomous representations of hypertension without an attempt to look at degree of blood pressure control. Aim: To determine the association between optimal blood pressure control over time and the development of erectile dysfunction (ED) in a cohort of potent men. Methods: We performed a retrospective cohort study of newly diagnosed hypertensive men without major medical comorbidities in an integrated healthcare system. Patients were stratified by exposure to hypertension, with varying levels of blood pressure control, as measured by ordinal categories of systolic blood pressure and deviation from the mean systolic pressure. Main Outcome Measures: Incidence of ED was defined by at least 2 primary care or urology diagnoses of ED in our electronic health records within 2 years, at least 2 filled prescriptions for ED medications within 2 years, or 1 diagnosis of ED and 2 filled prescriptions for ED medications. Results: We identified 39, 320 newly diagnosed hypertensive men. The overall incidence for ED was 13.9%, with a mean follow-up of 55.1 ± 28.7 months. Higher average systolic blood pressure was associated with a higher risk of ED in a dose-dependent manner (trend test, P < .001). Wide variation in blood pressure control was associated with a higher incidence of ED (OR [95% CI]; 1.359 [1.258–1.469]) and a shorter time to the development of ED (log rank, P < .0001). Clinical Implications: We believe these data may serve as a motivator for hypertensive men to better adhere to their hypertension treatment regimen. Strength & Limitations: The retrospective nature of our study precludes us from drawing more than an association between tighter blood pressure control and ED. Strengths of our study include the large sample size, community cohort, and completeness of follow-up. Conclusion: Among adults diagnosed with hypertension, tighter blood pressure control, as measured by average systolic blood pressure and deviation from the average, is associated with a lower incidence and a longer time to the development of ED.